Magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material as well as preparation method and application thereof
By developing magnetic chitosan/AlOOH/polyethylene polyamine-grade porous structural composite materials, the problem of limited fluorine ion adsorption capacity and susceptibility to interference in fluorine-containing wastewater treatment in the prior art is solved, and efficient and stable fluorine ion adsorption and removal effects are achieved.
Patent Information
- Application Number
- CN202510176434.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, when treating fluorine-containing wastewater, the adsorption capacity of the adsorbent on fluorine ions is limited and is easily disturbed by coexisting anions and cations, which affects the fluorine removal performance.
A magnetic chitosan/AlOOH/polyethylene polyamine graded porous structure composite material was developed. Through the mixed cross-linking reaction of chitosan with Fe3O4 and aluminum salt, AlOOH was grown in situ under an alkaline environment, and the polyethylene polyamine cross-linked by glutaraldehyde to form a composite material with a graded porous structure.
The composite material has excellent fluoride ion adsorption performance, stable structure and good reuse performance. It can achieve a fluoride ion removal rate of 96% within 4 hours, and is suitable for actual industrial fluorine-containing wastewater treatment.
Smart Images

Figure HDA0005275666030000011 
Figure HDA0005275666030000021 
Figure HDA0005275666030000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluorine-containing wastewater treatment, and specifically relates to a magnetic chitosan / AlOOH / polyethylene polyamine graded porous structure composite material and a preparation method and application thereof. Background Art
[0002] Industrial production such as electroplating, aluminum electrolysis, semiconductors, and steel will produce a large amount of fluoride-containing wastewater. The fluoride ion concentration in these wastewaters can reach 10-10000 mg / L. If they are discharged directly without treatment, they will cause great harm to the ecological environment. At present, the main methods for treating fluoride-containing wastewater are chemical precipitation, coagulation precipitation, membrane separation, electrocoagulation, ion exchange, and adsorption. The adsorption method uses the electrostatic interaction, ion exchange, or complexation between the adsorbent and the fluoride ions to adsorb the fluoride ions to the surface of the material, thereby achieving the purpose of enriching, concentrating, and removing fluoride ions in water. It has the advantages of simple operation and high removal efficiency.
[0003] According to Pearson's hard and soft acid-base (HSAB) theory, aluminum (III) (hard Lewis acid) has a strong affinity for fluoride ions (hard Lewis bases) with high electronegativity and small ion size. Therefore, aluminum-containing fluoride ion adsorbents have been studied in depth. Activated alumina is widely used due to its porous structure and high specific surface area, but its adsorption capacity for fluoride ions is only 1.1 to 3.0 mg / g, and alumina is prone to dissolution during use. In addition to alumina, studies have also reported the adsorption of fluoride ions by aluminum hydroxide-based materials such as cellulose / Al(OH)3 composites. With the increase of Al(OH)3 loading, the adsorption capacity of fluoride ions can be increased to 20 mg / g, indicating that Al(OH)3 can improve the adsorption performance of the adsorbent for fluoride ions, but there is a problem of long adsorption equilibrium time. In addition, actual fluoride-containing wastewater also contains a large amount of coexisting anions and cations (SO4 2- 、NO3 - , Cl - 、CO3 2- PO4 3- , Ca 2+ and Mg 2+ ), which may affect the defluorination performance of the adsorbent. Therefore, it is necessary to research and develop an adsorbent with high defluorination efficiency, stable structure, strong anti-interference ability, and can be applied to actual wastewater.
[0004] Chitosan is a natural polymer that contains a large number of amino groups and hydroxyl groups in its molecular chain. It has good adsorption capacity for anionic pollutants in water. Some researchers have prepared chitosan / iron / aluminum / manganese composite materials and found that the adsorption capacity of the adsorbent for fluoride ions is 40 mg / g. Although the adsorbent has good defluorination performance, there is a problem that the powdered adsorbent is difficult to recycle. Polyethylene polyamine is a co-product of ethylenediamine, diethylenetriamine, triethylenetetramine and tetraethylenepentamine. It is a polymer with a hyperbranched structure and a large number of amino groups. It is often used for chitosan modification and removal of anionic pollutants in water. The use of polyethylene polyamine to modify chitosan can effectively improve the adsorption performance, mechanical strength, functional diversity and reusability of chitosan. The modified material shows excellent performance in many fields, including dye adsorption and heavy metal ion adsorption. For example, CN116836427A discloses a porous chitosan film rich in Schiff base functional groups, a preparation method and application thereof. Methods Chitosan was used as the main raw material and nanospheres were used as hard templates. Dispersion made into thin film. The nano-microspheres are removed by chemical reagent treatment to prepare a porous chitosan film. Polyethylene polyamine is further introduced into the surface of the porous film by a crosslinking agent, and then crosslinked by glutaraldehyde, and finally a porous chitosan film with a unique pore structure and rich in Schiff base functional groups on the surface is obtained. The porous chitosan film can be used to remove or recover a variety of metal ions in wastewater, and solve the problem of water pollution. CN110215907A also discloses a chitosan / γ-AlOOH composite film for adsorbing Pb(II) in water, and its preparation method and application. After preparing γ-AlOOH sol, the sol is mixed with chitosan sol, glutaraldehyde is added, and a crosslinking reaction is carried out. After tape casting and drying, a chitosan / γ-AlOOH composite film is obtained. The chitosan / γ-AlOOH composite film has a larger adsorption amount and a higher adsorption rate for Pb(II) in water, and a stronger acid resistance.
[0005] Based on the above, the present invention provides a chitosan / AlOOH / polyethylene polyamine composite material with multifunctional groups, magnetic responsiveness, structural stability and hierarchical porous structure, and applies the composite material to the adsorption of fluoride ions in wastewater. Summary of the invention
[0006] In view of the above problems, the present invention provides a magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material and its preparation method and application. The composite material has a stable structure, good reusability and excellent adsorption performance for fluoride ions.
[0007] The present invention is achieved through the following technical solutions:
[0008] A magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material is provided. Chitosan, Fe3O4 and aluminum salt are mixed, epichlorohydrin is added for cross-linking reaction, AlOOH is grown in situ in an alkaline environment, and chitosan is precipitated, aggregated and separated to obtain magnetic chitosan / AlOOH; glutaraldehyde is used as a cross-linking agent to cross-link and graft polyethylene polyamine on the magnetic chitosan / AlOOH to obtain the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material.
[0009] Furthermore, the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material has a hierarchical porous structure, and has macropores greater than 500 nm and a mesoporous structure with an average pore size of 16.2 to 16.3 nm, and a pore volume of 0.009 to 0.01 cm 3 / g, specific surface area is 3.0~3.1m 2 / g, and the saturation magnetization value is 4.3~4.4emu / g.
[0010] A method for preparing the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material as described above comprises the following steps:
[0011] (1) Preparation of magnetic chitosan / AlOOH: Fe3O4 magnetic particles are ultrasonically dispersed in water, chitosan powder is added, glacial acetic acid is added under stirring, and the mixture is stirred until it is dissolved and dispersed uniformly. Then, aluminum salt is added, and after stirring and dissolving, epichlorohydrin is added for cross-linking reaction. The pH of the solution is adjusted to alkaline. After the reaction is completed, the mixture is separated by a magnet, and the magnetic chitosan / AlOOH is obtained after washing and drying.
[0012] (2) Preparation of magnetic chitosan / AlOOH / polyethylene polyamine: Magnetic chitosan / AlOOH is added to glutaraldehyde for reaction, and then polyethylene polyamine is added for grafting reaction. After stirring, the mixture is separated by a magnet. After washing and drying, a magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material is obtained.
[0013] Furthermore, in step (1), the aluminum salt is one or two of aluminum chloride, polyaluminum chloride, and aluminum sulfate.
[0014] Furthermore, in step (1), the mass volume ratio of the Fe3O4 magnetic particles, chitosan powder, aluminum salt and epichlorohydrin is 0.1-0.3 g:1-3 g:1-2 g:2 mL; the mass volume ratio of the chitosan powder and glacial acetic acid is 1-3 g:2 mL.
[0015] Furthermore, in step (1), the temperature of the cross-linking reaction is 30 to 60° C., and the time is 3 to 6 hours.
[0016] Furthermore, in step (1), the pH of the solution is adjusted to alkaline by using 5-10% by mass of ammonia water to adjust the pH of the solution to 8-9.
[0017] Furthermore, in step (2), the mass volume ratio of the magnetic chitosan / AlOOH to glutaraldehyde is 0.5-1 g:2 mL; the mass volume ratio of the polyethylene polyamine to glutaraldehyde is 0.5-1 g:2 mL, and the concentrations of polyethylene polyamine and glutaraldehyde are both 40-50%.
[0018] Furthermore, in step (2), the temperature of the grafting reaction is 40-70° C., and the time is 4-8 hours; and the time for reacting the magnetic chitosan / AlOOH in glutaraldehyde is 0.5-2 hours.
[0019] An application of the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material in adsorbing and removing fluoride ions from fluoride-containing wastewater.
[0020] The preparation principle of the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material of the present invention is as follows:
[0021] (1) Preparation of magnetic chitosan / AlOOH: Chitosan was dissolved with glacial acetic acid, and then the amino and hydroxyl groups in the chitosan molecular structure were used to chelate aluminum ions and ferroferric oxide nanoparticles. The chitosan molecular chains were cross-linked with epichlorohydrin, and finally an ammonia solution was used to provide an alkaline environment to make aluminum ions grow in situ to form AlOOH, and chitosan was precipitated and aggregated to obtain magnetic chitosan / AlOOH. (2) Preparation of magnetic chitosan / AlOOH / polyethylene polyamine: Glutaraldehyde was used as a cross-linking agent to graft and cross-link polyethylene polyamine into the molecular structure of magnetic chitosan / AlOOH to obtain a magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material.
[0022] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0023] 1. The present invention mixes chitosan, Fe3O4 and aluminum salt, adds epichlorohydrin for cross-linking reaction, grows AlOOH in situ in an alkaline environment, and precipitates chitosan to obtain magnetic chitosan / AlOOH; then uses glutaraldehyde as a cross-linking agent to cross-link and graft polyethylene polyamine on the magnetic chitosan / AlOOH to obtain a magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material. The composite material has a hierarchical porous structure, and has macropores greater than 500nm and a mesoporous structure with an average pore size of 16.2-16.3nm, and a specific surface area of 3.0-3.1m 2 / g, the saturation magnetization value is 4.3-4.4emu / g, its structure is stable, the performance of repeated use is good, and it has excellent adsorption performance for fluoride ions in fluoride-containing wastewater.
[0024] 2. It can be seen from the SEM and BET characterization that the composite material of the present invention has both macroporous (>500nm) and mesoporous (average pore size: 16.25nm) structures, belonging to a hierarchical porous structure. This special structure is conducive to the rapid diffusion and adsorption of fluoride ions.
[0025] 3. In the composite material of the present invention, chitosan polymer acts as a carrier to chelate and complex with AlOOH, thereby improving the structural stability of AlOOH. Fe3O4 acts as a magnetic material with a stable structure, and after combining with chitosan, the composite material can be quickly separated and recovered in a solution, and the composite material has good reusability.
[0026] 4. The composite material of the present invention can effectively adsorb and remove fluoride ions from fluoride-containing wastewater. Its adsorption mechanism for fluoride ions is mainly electrostatic adsorption, ion exchange and coordination complexation. The chitosan has amino and hydroxyl groups, which can produce electrostatic and hydrogen bond adsorption for fluoride ions respectively; AlOOH and anion F - The coordination complexation is generated to form a F-AlOOH complex with Al-F coordination bonds, which has a selective adsorption effect on fluoride ions in fluoride-containing wastewater containing multiple coexisting anions; polyethylene polyamine contains a large number of amino groups, which produces electrostatic adsorption of fluoride ions. The composite material has a hierarchical porous structure and contains a large number of amino and hydroxyl functional groups, which is conducive to the rapid diffusion and adsorption of fluoride ions and shortens the adsorption equilibrium time.
[0027] 5. The preparation process of the present invention is simple, the operating conditions are mild, the raw materials are easily available, the cost is low, and it is suitable for industrial production. The composite material prepared by the present invention has excellent adsorption performance for fluoride ions, and the fluoride ion removal rate can reach 96% within 4 hours. The fluoride ion removal efficiency is high, and it has good practical application value in treating fluoride-containing wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the structure of MCA1P prepared in Example 1.
[0029] Figure 2 SEM images of CS, Fe3O4, AlOOH, MCAl prepared in Comparative Example 1, and MCAlP prepared in Example 1.
[0030] Figure 3 XRD patterns of CS, Fe3O4, AlOOH, MCAl prepared in Comparative Example 1, and MCAlP prepared in Example 1.
[0031] Figure 4 FT-IR graphs of CS, Fe3O4, AlOOH, MCAl prepared in Comparative Example 1, and MCAlP prepared in Example 1.
[0032] Figure 5 XPS charts of CS, Fe3O4, AlOOH, MCAl prepared in Comparative Example 1, and MCAlP prepared in Example 1.
[0033] Figure 6 1 is the hysteresis loop diagram of MCA1P obtained in Example 1.
[0034] Figure 7 It is the N2 adsorption-desorption curve diagram of CS, Fe3O4, AlOOH, MCAl prepared in Comparative Example 1 and MCAlP prepared in Example 1.
[0035] Figure 8 This is a graph showing the adsorption capacity of CS, Fe3O4, AlOOH, MCAl prepared in Comparative Example 1, and MCAlP prepared in Example 1 for fluoride ions. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below by way of examples. These examples are only used to illustrate the present invention and do not limit the protection scope of the present invention.
[0037] Example 1
[0038] Preparation of magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite materials:
[0039] (1) Preparation of magnetic chitosan / AlOOH: Weigh 0.1 g of Fe3O4 magnetic particles and ultrasonically disperse them in 100 mL of distilled water, add 1 g of chitosan (CS) powder, add 2 mL of glacial acetic acid under stirring, and stir until the mixture is dissolved and dispersed evenly. Add 1 g of aluminum chloride to the mixture and stir to dissolve. Then, add 2 mL of epichlorohydrin and cross-link at 30°C for 3 h. Then, drop 10% ammonia solution into the mixture until the pH of the mixture is 8.5. After stirring for 1 h, separate the mixture with a magnet, wash it, and dry it to obtain magnetic chitosan / AlOOH.
[0040] (2) Preparation of magnetic chitosan / AlOOH / polyethylene polyamine: 0.5 g of magnetic chitosan / AlOOH was added to 2 mL of 50% glutaraldehyde for reaction for 1 h, and then 0.5 g of 50% polyethylene polyamine was added for grafting reaction at 40° C. for 4 h. The mixture was separated by a magnet, washed with distilled water until the pH was neutral, and then dried to obtain a magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material (denoted as MCAlP). The schematic diagram of its structure is shown in FIG. Figure 1 shown.
[0041] Example 2
[0042] Preparation of magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite materials:
[0043] (1) Preparation of magnetic chitosan / AlOOH: Weigh 0.2 g of Fe3O4 magnetic particles and ultrasonically disperse them in 100 mL of distilled water, add 1.5 g of chitosan powder, add 2 mL of glacial acetic acid under stirring, and stir until the mixture is dissolved and dispersed evenly. Add 1.5 g of aluminum chloride to the mixture and stir to dissolve it. Then, add 2 mL of epichlorohydrin and cross-link at 40°C for 4 h. Then, drop 10% ammonia solution into the mixture until the pH of the mixture is 8.3. After stirring for 1 h, separate the mixture with a magnet, wash it, and dry it to obtain magnetic chitosan / AlOOH.
[0044] (2) Preparation of magnetic chitosan / AlOOH / polyethylene polyamine: 0.7 g of magnetic chitosan / AlOOH was added to 2 mL of 45% glutaraldehyde for reaction for 1 h, and then 0.7 g of 45% polyethylene polyamine was added for grafting reaction at 50°C for 5 h. The mixture was separated by a magnet, rinsed with distilled water until the pH was neutral, and then dried to obtain a magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material.
[0045] Example 3
[0046] Preparation of magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite materials:
[0047] (1) Preparation of magnetic chitosan / AlOOH: Weigh 0.25 g of Fe3O4 magnetic particles and ultrasonically disperse them in 100 mL of distilled water, add 2 g of chitosan powder, add 2 mL of glacial acetic acid under stirring, and stir until dissolved and dispersed uniformly. Add 1.5 g of aluminum sulfate to the mixture, stir and dissolve, add 2 mL of epichlorohydrin and cross-link at 45°C for 4.5 h, dropwise add 8% ammonia solution until the pH of the mixture is 8.1, stir for 1 h, separate with a magnet, wash and dry to obtain magnetic chitosan / AlOOH.
[0048] (2) Preparation of magnetic chitosan / AlOOH / polyethylene polyamine: 0.8 g of magnetic chitosan / AlOOH was added to 2 mL of 50% glutaraldehyde and reacted for 1 h. Then, 0.8 g of 45% polyethylene polyamine was added and grafted at 60°C for 4 h. The mixture was separated by a magnet, rinsed with distilled water until the pH was neutral, and then dried to obtain a magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material.
[0049] Example 4
[0050] Preparation of magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite materials:
[0051] (1) Preparation of magnetic chitosan / AlOOH: Weigh 0.3 g of Fe3O4 magnetic particles and ultrasonically disperse them in 100 mL of distilled water, add 2 g of chitosan powder, add 2 mL of glacial acetic acid under stirring, and stir until the mixture is dissolved and dispersed uniformly. Add 2 g of aluminum chloride to the mixture and stir to dissolve. Then, add 2 mL of epichlorohydrin and cross-link at 50°C for 6 h. Then, drop 10% ammonia solution into the mixture until the pH value is 8.1. After stirring for 1 h, separate the mixture with a magnet, wash it, and dry it to obtain magnetic chitosan / AlOOH.
[0052] (2) Preparation of magnetic chitosan / AlOOH / polyethylene polyamine: 1 g of magnetic chitosan / AlOOH was added to 2 mL of 40% glutaraldehyde for reaction for 1 h, and then 1 g of 40% polyethylene polyamine was added for grafting reaction at 60°C for 7 h. The mixture was separated by a magnet, rinsed with distilled water until the pH was neutral, and then dried to obtain a magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material.
[0053] Comparative Example 1
[0054] Preparation of magnetic chitosan / AlOOH:
[0055] Weigh 0.1g of Fe3O4 magnetic particles and ultrasonically disperse them in 100mL of distilled water, add 1g of chitosan powder, add 2mL of glacial acetic acid under stirring, stir until dissolved and dispersed evenly, add 1g of aluminum chloride to the mixture, stir and dissolve, add 2mL of epichlorohydrin and cross-link at 30°C for 3h, drop 10% ammonia solution until the pH of the mixture is 8.5, stir for 1h, separate with a magnet, wash and dry to obtain magnetic chitosan / AlOOH (denoted as MCAl).
[0056] Material Characterization Analysis
[0057] (I) SEM analysis
[0058] Scanning electron microscopy (SEM) was used to characterize CS, Fe3O4, AlOOH, MCAl prepared in Comparative Example 1, and MCAlP prepared in Example 1. Figure 2 As shown. Figure 2It can be seen that the surface of chitosan is smooth; the particle size of Fe3O4 is about tens of nanometers, and the agglomeration and accumulation phenomenon is serious; the surface of AlOOH is uneven, and it is composed of accumulated nanoparticles, and the agglomeration phenomenon is serious. The surface of MCAl is rough and porous, and Fe3O4 nanoparticles and AlOOH particles are dispersed on the surface and inside. This shows that CS as a carrier has a good dispersing effect on Fe3O4 and AlOOH, which can increase the specific surface area of the adsorbent and help improve the adsorption capacity of the adsorbent. This is because CS has a large number of amino and hydroxyl functional groups, which can react with Fe3O4 and AlOOH. 3+ Chelation and complexation can achieve uniform dispersion. MCAl is cross-linked with polyethylene polyamine to form MCAlP, which has a large pore size (>500nm), a hierarchical porous structure, and a rougher surface than MCAl, which is conducive to further improving the adsorption performance.
[0059] (ii) XRD analysis
[0060] The crystal structures of CS, Fe3O4, AlOOH, MCAl prepared in Comparative Example 1 and MCAlP prepared in Example 1 were characterized by X-ray diffractometer (XRD). Figure 3 As shown. Figure 3 It can be seen that CS has a prominent crystal structure diffraction peak near 2θ = 20°, which is related to the (040) crystal plane of chitosan. Fe3O4 has specific diffraction peaks at 2θ = 18.2, 30.1, 35.6, 43.1, 53.6, 57.1 and 62.7°, which are consistent with the (111), (220), (311), (400), (422), (511) and (440) diffraction peaks of Fe3O4 crystal plane. As for AlOOH, specific diffraction peaks were observed at 2θ = 14.5, 28.2, 38.3, 49.2, 65.1 and 71.9°, which belong to the (020), (120), (031), (051), (002) and (251) crystal planes, respectively, which are consistent with the data of AlOOH standard card (JCPDS No. 21-1307). The spectrum of MCAl contains the characteristic peaks of CS, Fe3O4 and AlOOH, indicating that MCAl was successfully prepared. There is almost no difference between the crystal structures of MCAl and MCAlP, indicating that cross-linking and grafting MCAl with polyethylene polyamine will not change its crystal structure.
[0061] (III) FT-IR analysis
[0062] Fourier transform infrared spectrometer (FT-IR) was used to characterize CS, Fe3O4, AlOOH, MCAl prepared in Comparative Example 1 and MCAlP prepared in Example 1 to determine the functional groups of the materials. The results are as follows: Figure 4 As shown. Figure 4It can be seen from the CS spectrum that at 3444cm -1 The relatively broad bands at 1654 and 1423 cm-1 can be attributed to the stretching vibrations of -NH2 and -OH in the CS molecular structure. -1 The peaks at 572 cm represent the amide vibration, C=O stretching vibration and CH bending vibration of -NHCOCH3. -1 There is an obvious peak at 3446cm -1 The adsorption peak observed at 1072 cm belongs to the stretching vibration of the -OH group in AlOOH. -1 The sharp peak at 749, 628 and 483 cm-1 is attributed to the stretching vibration of the Al-OH bond, while -1 The peaks at 3444 and 1654 cm-1 in CS are related to the vibration of Al-O bonds. -1 The peaks at 3434 and 1634 cm -1 In AlOOH, 1072 and 483 cm -1 The adsorption peaks at 1078 and 488 cm -1 In addition, 572cm in Fe3O4 -1 The characteristic peak at 566 cm -1 The changes in these characteristic peaks indicate that CS is chelated and cross-linked with AlOOH and Fe3O4 through amino and hydroxyl groups, rather than simply physically mixed. After MCAl and polyethylene polyamine undergo cross-linking and grafting reactions to form MCAlP, the peaks at 3434 cm in MCAl are observed. -1 The peak at 3436 cm was transferred to 3436 cm in MCAlP. -1 , and the intensity increased, which indicated that the density of NH groups increased after MCAl was cross-linked with polyethylene polyamine. In addition, the spectrum of MCAlP contained the characteristic peaks of AlOOH and Fe3O4, which indicated that MCAlP had been synthesized.
[0063] (IV) XPS analysis
[0064] X-ray photoelectron spectroscopy (XPS) was used to characterize CS, Fe3O4, AlOOH, MCAl prepared in Comparative Example 1, and MCAlP prepared in Example 1. The results are as follows: Figure 5 As shown. Figure 5It can be seen that the XPS full scan spectra of CS, Fe3O4, AlOOH, MCAl and MCAlP contain C and O elements; CS, MCAl and MCAlP contain N element; Al element is only contained in AlOOH, MCAl and MCAlP; the characteristic peak of iron element in MCAl and MCAlP is not obvious, which may be because the content of Fe3O4 is relatively low; but XRD analysis and detection show that Fe3O4 crystal diffraction peak exists in both MCAl and MCAlP.
[0065] (V) VSM analysis
[0066] The hysteresis loop of the MCA1P obtained in Example 1 was measured using a vibrating sample magnetometer (VSM). Figure 6 As shown. Figure 6 As can be seen from the figure, the saturation magnetization value of MCAlP is 4.36emu / g; as can be seen from the inset, MCAlP can be effectively attracted by the magnet, which indicates that MCAlP has excellent magnetic responsiveness and can be quickly separated from aqueous solution.
[0067] (VI) Specific surface area and pore structure analysis
[0068] The adsorption-desorption curves, pore volumes and pore size distributions of CS, Fe3O4, AlOOH, MCAl prepared in Comparative Example 1 and MCAlP prepared in Example 1 were determined by N2 adsorption isotherms. The results are as follows: Figure 7 As shown. Figure 7 It can be seen that the specific surface areas of CS, Fe3O4 and AlOOH are 0.77, 10.27 and 337.05 m 2 / g; the specific surface area of MCAl is 1.78m 2 / g, which indicates that in the process of synthesizing MCAl, the addition of Fe3O4 and AlOOH did not significantly increase the specific surface area of CS; it also means that Fe3O4 and AlOOH are tightly combined with CS and evenly distributed, and Fe3O4 and AlOOH are not simply physically mixed with CS, but strongly interact with each other. This makes Fe3O4 and AlOOH embedded in CS, which is beneficial to improve the structural stability of MCAlP. Compared with MCAl, the specific surface area of MCAlP increased by 1.28m 2 / g, which may be due to the formation of polyethylene polyamine particles after cross-linking with MCAl. The pore volumes of CS, Fe3O4, AlOOH, MCAl and MCAlP are 0.0038, 0.036, 0.05673, 0.0058 and 0.0092 cm 3 / g, the pore sizes of CS, Fe3O4, AlOOH, MCAl and MCAlP are 27.31, 15.1, 6.03, 8.17 and 16.25nm respectively. Compared with CS, the addition of Fe3O4 and AlOOH can significantly increase the pore volume of CS and reduce the pore size, which is beneficial to the diffusion and adsorption of fluoride ions. Most importantly, according to SEM and BET characterization, it can be seen that MCAlP has both macroporous (>500nm) and mesoporous (average pore size: 16.25nm) structures, so MCAlP is a hierarchical porous structure, and this special structure will also promote the rapid adsorption of fluoride ions.
[0069] Application Example 1
[0070] 50 mg of the magnetic chitosan / AlOOH / polyethylene polyamine prepared in Example 1 was placed in fluoride-containing wastewater with a pH of 3.5, a volume of 50 mL, and a fluoride ion concentration of 10 mg / L for adsorption reaction for 4 hours, and the fluoride ion removal rate was measured to be 94%.
[0071] Application Example 2
[0072] 50 mg of the magnetic chitosan / AlOOH / polyethylene polyamine prepared in Example 2 was placed in fluoride-containing wastewater with a pH of 4.5, a volume of 50 mL, and a fluoride ion concentration of 12 mg / L for adsorption reaction for 4 hours, and the fluoride ion removal rate was measured to be 93%.
[0073] Application Example 3
[0074] 50 mg of the magnetic chitosan / AlOOH / polyethylene polyamine prepared in Example 3 was placed in fluoride-containing wastewater with a pH of 4.0, a volume of 50 mL, and a fluoride ion concentration of 11 mg / L for adsorption reaction for 5 hours, and the fluoride ion removal rate was measured to be 96%.
[0075] Application Example 4
[0076] 50 mg of the magnetic chitosan / AlOOH / polyethylene polyamine prepared in Example 4 was placed in fluoride-containing wastewater with a pH of 4.2, a volume of 50 mL, and a fluoride ion concentration of 14 mg / L for adsorption reaction for 5 hours, and the fluoride ion removal rate was measured to be 95%.
[0077] Application Comparative Example 1
[0078] 50 mg of the magnetic chitosan / AlOOH prepared in Comparative Example 1 was placed in fluoride-containing wastewater with a pH of 3.5, a volume of 50 mL, and a fluoride ion concentration of 10 mg / L for adsorption reaction for 4 hours, and the fluoride ion removal rate was measured to be 70.8%.
[0079] Application Comparative Example 2
[0080] 50 mg of chitosan was placed in fluoride-containing wastewater with a pH of 3.5, a volume of 50 mL, and a fluoride ion concentration of 10 mg / L for adsorption reaction for 4 hours, and the fluoride ion removal rate was measured to be 23.7%.
[0081] Application Comparative Example 3
[0082] 50 mg of Fe3O4 was placed in fluoride-containing wastewater with a pH of 3.5, a volume of 50 mL, and a fluoride ion concentration of 10 mg / L for adsorption reaction for 4 hours, and the fluoride ion removal rate was measured to be 4.79%.
[0083] Application Comparative Example 4
[0084] 50 mg of AlOOH was placed in fluoride-containing wastewater with a pH of 3.5, a volume of 50 mL, and a fluoride ion concentration of 10 mg / L for adsorption reaction for 4 hours, and the fluoride ion removal rate was measured to be 58.8%.
[0085] Material application analysis
[0086] The adsorption of fluoride ions in fluoride-containing wastewater by the adsorbent materials in Application Example 1 and Application Comparative Examples 1-4 was analyzed. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that the adsorption capacity of CS, Fe3O4, AlOOH, MCAl, and MCAlP for fluoride ions are 8.9, 1.8, 22.1, 26.6, and 35.3 mg / g, respectively. Compared with AlOOH, the adsorption capacity of MCAlP and MCAl increased by 13.2 and 4.5 mg / g, respectively, indicating that polyethylene polyamine and chitosan can significantly increase the adsorption capacity of AlOOH for fluoride ions.
[0087] In summary, the present invention uses chitosan as a carrier and constructs a magnetic chitosan / AlOOH / polyethylene polyamine adsorbent with a hierarchical porous structure, multiple functional groups and structural stability through chelation, cross-linking and immobilization strategies to efficiently remove fluoride ions in wastewater, achieving the expected effect, and will have broad application prospects in the actual treatment of industrial fluoride-containing wastewater.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material, characterized in that: After chitosan, Fe3O4 and aluminum salt are mixed, epichlorohydrin is added for cross-linking reaction, AlOOH is grown in situ in an alkaline environment, and chitosan is precipitated and aggregated to obtain magnetic chitosan / AlOOH; glutaraldehyde is used as a cross-linking agent to cross-link and graft polyethylene polyamine on the magnetic chitosan / AlOOH to obtain a magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material.
2. The magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material according to claim 1, characterized in that: The magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material has a hierarchical porous structure, and has macropores greater than 500 nm and a mesoporous structure with an average pore size of 16.2 to 16.3 nm, and a pore volume of 0.009 to 0.01 cm 3 / g, specific surface area is 3.0~3.1m 2 / g, and the saturation magnetization value is 4.3~4.4emu / g.
3. A method for preparing the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of magnetic chitosan / AlOOH: Fe3O4 magnetic particles are ultrasonically dispersed in water, chitosan powder is added, glacial acetic acid is added under stirring, and the mixture is stirred until it is dissolved and dispersed uniformly. Then, aluminum salt is added, and after stirring and dissolving, epichlorohydrin is added for cross-linking reaction. The pH of the solution is adjusted to alkaline. After the reaction is completed, the mixture is separated by a magnet, and the magnetic chitosan / AlOOH is obtained after washing and drying. (2) Preparation of magnetic chitosan / AlOOH / polyethylene polyamine: Magnetic chitosan / AlOOH is added to glutaraldehyde for reaction, and then polyethylene polyamine is added for grafting reaction. The mixture is then separated by a magnet, washed and dried to obtain a magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material.
4. The method for preparing the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material according to claim 3, characterized in that: In step (1), the aluminum salt is one or two of aluminum chloride, polyaluminum chloride, and aluminum sulfate.
5. The method for preparing the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material according to claim 4, characterized in that: In step (1), the mass volume ratio of the Fe3O4 magnetic particles, chitosan powder, aluminum salt and epichlorohydrin is 0.1-0.3g:1-3g:1-2g:2mL; the mass volume ratio of the chitosan powder and glacial acetic acid is 1-3g:2mL.
6. The method for preparing the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material according to claim 3, characterized in that: In step (1), the temperature of the cross-linking reaction is 30 to 60° C. and the time is 3 to 6 hours.
7. The method for preparing the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material according to claim 3, characterized in that: In step (1), the pH of the solution is adjusted to alkaline by using 5-10% by mass aqueous ammonia to adjust the pH of the solution to 8-9.
8. The method for preparing the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material according to claim 3, characterized in that: In step (2), the mass volume ratio of the magnetic chitosan / AlOOH to glutaraldehyde is 0.5-1 g:2 mL; the mass volume ratio of the polyethylene polyamine to glutaraldehyde is 0.5-1 g:2 mL, and the concentrations of the polyethylene polyamine and glutaraldehyde are both 40-50%.
9. The method for preparing the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material according to claim 3, characterized in that: In step (2), the temperature of the grafting reaction is 40-70° C., and the reaction time is 4-8 hours; and the reaction time of adding magnetic chitosan / AlOOH to glutaraldehyde is 0.5-2 hours.
10. Use of the magnetic chitosan / AlOOH / polyethylene polyamine hierarchical porous structure composite material as claimed in claim 1 or 2 in the adsorption and removal of fluoride ions in fluoride-containing wastewater.
Citation Information
Patent Citations
Chitosan / gamma-AlOOH composite thin film for absorbing Pb(II) in water and preparation method and application thereof
CN110215907A
Porous chitosan film rich in Schiff base functional group as well as preparation method and application of porous chitosan film
CN116836427A
Cited By
Polyaluminum chloride water purifying agent and preparation method thereof
CN120757208A